Comparison of palbociclib in combination with letrozole or fulvestrant with endocrine therapies for advanced/metastatic breast cancer: network meta-analysis. (3rd August 2017) - Chirila, Costel; Mitra, Debanjali; Colosia, Ann; Ling, Caroline; Odom, Dawn; Iyer, Shrividya; Kaye, James A.
Abstract: Background: Palbociclib is the first cyclin-dependent kinase 4/6 inhibitor approved in the United States for HR+/HER2- advanced/metastatic breast cancer, in combination with letrozole as initial endocrine-based therapy in postmenopausal women or with fulvestrant in women with disease progression following endocrine therapy. We compared progression-free survival (PFS) and discontinuations due to adverse events for palbociclib combinations against other endocrine therapies using a mixed-treatment comparison meta-analysis of randomized, controlled trials. Methods: A systematic literature review identified relevant trials. Separate analyses were conducted for each palbociclib combination using a Bayesian approach. Treatment rankings were established using the surface under the cumulative ranking curve (SUCRA). Results: Sixty-five unique studies met inclusion criteria. Palbociclib plus letrozole had the highest SUCRA value (99.9%) and was associated with significantly longer PFS than all comparators in treatment-naïve patients (hazard ratios [HRs] ranged from 0.41 to 0.58). Palbociclib plus fulvestrant had the second highest SUCRA value (93.9%) and, in previously treated patients, yielded significantly longer PFS than most comparators (HRs ranged from 0.26 to 0.46); the exception was everolimus plus exemestane, with similar PFS (HR, 1.04; 95% credible interval [CrI], 0.58–1.76). Palbociclib plus fulvestrant was associated with significantly lower odds of discontinuation due to adverse events than everolimus plus exemestane (odds ratio, 0.14; 95% CrI, 0.05–0.39). Conclusions: The results suggest that the two palbociclib combinations yielded significantly greater PFS than endocrine therapy in treatment-naïve and previously treated patients with advanced/metastatic breast cancer. Palbociclib plus fulvestrant was associated with significantly less toxicity than everolimus plus exemestane.